2012
DOI: 10.1111/j.1537-2995.2011.03553.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of improved hepatitis B surface antigen detection limits with hepatitis B virus DNA nucleic acid test yield in blood donations

Abstract: Increased sensitivity HBsAg assays result in the detection of samples containing lower viral loads. Improvements in the analytic sensitivity of HBsAg prototype assays allow the detection of additional HBV DNA-positive samples from donors with window period or occult infections compared to PRISM HBsAg. Improved HBsAg assays should allow for incremental detection of HBV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…The HBV DNA concentration in all OBI donors was 40 IU/mL or lower. Higher HBsAg assay sensitivity would be required to detect possible HBsAg in infected individuals having such low viral loads (e.g., 0.02 ng/mL vs. 0.08–0.10 ng/mL of current assays) . OBI donors who are HBV DNA positive provide ongoing evidence that they may be “currently” infected and therefore potentially infectious.…”
Section: Discussionmentioning
confidence: 99%
“…The HBV DNA concentration in all OBI donors was 40 IU/mL or lower. Higher HBsAg assay sensitivity would be required to detect possible HBsAg in infected individuals having such low viral loads (e.g., 0.02 ng/mL vs. 0.08–0.10 ng/mL of current assays) . OBI donors who are HBV DNA positive provide ongoing evidence that they may be “currently” infected and therefore potentially infectious.…”
Section: Discussionmentioning
confidence: 99%
“…Testing for HBsAg was initiated in the early 1970s with, at that time, assays detecting HBs concentrations higher than 1000 ng/ml. Current available assays achieve a limit of detection lower than 0·1 ng/ml with an estimated viral load at assay cut‐off under 300 copies/ml, that is equivalent to the threshold of NAT methods when performed in mini‐pools . It should be noted, however, that in spite of a very high level of sensitivity, HBsAg assays may be affected by HBV variants bearing substitutions in the amino acids sequence of HBs protein, which prevent binding to anti‐HBs monoclonal antibodies (Ab) that are used in immunoassays .…”
Section: Screening Testingmentioning
confidence: 99%
“…Besides approximately 40% of individuals with this pro le of results, this serological marker has low speci city and high rates of false-positives, requiring additional con rmatory tests such as molecular tests to retain the result (25)(26). In contrast, several studies have shown that Anti-HBc is the only serological marker found in occult infection with NAT negative HBV, being considered an important complement to transfusion safety (20,(27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%